1997
DOI: 10.1017/s0022215100138459
|View full text |Cite
|
Sign up to set email alerts
|

The Groote Schuur hospital classification of the orbital complications of sinusitis

Abstract: The complications of sinusitis have been well described. The most common classifications used for orbital complications have been that of Chandler et al. (1970) and Moloney et al. (1987). With the ready availability of high-resolution computed tomography (CT) scanners, limitations of these classifications have become apparent. The aims of this study were to determine the relative frequency of the various complications associated with acute sinusitis, to determine which groups of sinuses were most frequently in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
50
1
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 21 publications
10
50
1
11
Order By: Relevance
“…All the patients survived, but 11% became blind due to panophthalmitis and 16% had to have destructive surgeries. This is at variance with the study of Mortimore et al who had a 26% incidence of blindness 9 . The diagnosis of alveolar rhabdomyosarcomas on histology of specimen obtained during antrostomy highlights the importance of subjecting every specimen no matter how 'insignificant' to histology.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…All the patients survived, but 11% became blind due to panophthalmitis and 16% had to have destructive surgeries. This is at variance with the study of Mortimore et al who had a 26% incidence of blindness 9 . The diagnosis of alveolar rhabdomyosarcomas on histology of specimen obtained during antrostomy highlights the importance of subjecting every specimen no matter how 'insignificant' to histology.…”
Section: Discussioncontrasting
confidence: 80%
“…The most common pattern of sinus involvement causing orbital cellulitis was the combination of maxillary, ethmoidal and frontal sinuses (multisinusitis) which is similar to the result of Mortimore et al 9 However, the ethmoidal and maxillary sinuses were most frequently involved in the study by Swift et al 13 The multiple sinus involvement is probably an indication of the severity of the infection and the continuous nature of the mucosal lining of the paranasal sinuses.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This is in keeping with the universal acceptance of this organism as a major pathogen. [3][4][5][6][7][8]11,14,15 H. influenzae (8.6%) and coagulase-negative staphylococci (8.6%) ranked joint third. H. influenzae occurred more frequently in children than in adults (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…2,9 This study identified only one isolate of M. catarrhalis (0.4%), which supports the consensus that this organism is not a major pathogen in complicated sinusitis. 1,[3][4][5][6][11][12][13][14] Anaerobic bacteria may account for as much as one-third of all isolates. 5,6 In this study they accounted for 13.3% (Table I).…”
Section: Discussionmentioning
confidence: 99%